ETHNOSCIENCE STUDIES IN THE PROCESS OF MAKING LAKLAK IN SADING VILLAGE AS SUPPORTING MATERIAL FOR JUNIOR HIGH SCHOOL SCIENCE LEARNING - Ni Luh Gede Nindiana Sephia Dewi; Putri Sarini; Luh Mitha Priyanka (Jurnal IPA Terpadu, 2024)
This research aims to describe and explain ethnoscience studies in the process of making laklak in Sading Village as support for junior high school science learning materials. This research uses qualitative research with an ethnography approach. The research was carried out in Sading Village, Badung. Determining the respondents in this study used purposive sampling and snowball sampling techniques obtained from 3 laklak producers and using techniques purposive sampling obtained 3 science teachers at SMP Negeri 5 Mengwi. The data collection techniques used were observation, interviews, documentation and questionnaires. Data analysis techniques use the Miles and Huberman model, including data reduction, data presentation, and drawing conclusions. The results of the research show that the process of making laklak in Sading Village consists of several stages, including making suji leaf water, making laklak dough, baking laklak and serving laklak. The results of scientific studies from making laklak in Sading Village can be supporting material in junior high school science learning, that is classification of living things, pressure of substances, classification of matter and its changes, heat and its displacement, simple businesses and planes, movement systems in humans, food and the human digestive system, additives, and air pollution.